APLIKASI PERINGATAN BENCANA BANJIR BERBASIS ANDROID - Feri susilawati; Zaid Haritsah; Safwan (Politeknik Aceh, 2020)
Many victims are caused by floods every year due to inadequate warning systems that exist today. Making a flood disasterwarning application is used to receive information in the form of the latest water level conditions that are designed usingultra sonic sensors, So as to minimize the number of flood victims. Ultrasonic sensors detect water levels above 11cm, soArduino sends a signal to Android to instruct the Android to send a water warning SMS that has reached the standby pointto the user using the SMS Gateway Method, so users can receive SMS notifications about water levels in real time.